Towards a unified formal model for supporting mechanisms of dynamic component update Full text PdfPdf (268 KB). - Shen, Junrong (Software engineering notes.)
The continuous requirements of evolving a delivered software system and the rising cost of shutting down a running software system are forcing researchers and practitioners to find ways of updating software as it runs. Dynamic update is a kind of software evolution that updates a running program without interruption. This paper covers the fundamental issues of the mechanisms of dynamic update theoretically. Based on a similarity analysis of many typical approaches to dynamic update during the past decades, we propose a unified formal model (namely, Dynamic Update Connector) to specify mechanisms of updating an architectural component, and reason about its properties. The model borrows the concept of connectors from software architecture community and is specified using process algebra CSP. We also demonstrate the applications of our DUC model.